Self-assessment throughvideo-recorded speech rehearsals in delivering technical oral presentation - Benraghda, Abdelmadjid (2019)
The present study embarked upon the issue of the effectiveness of self-assessment in developing non-verbal communication skills among engineering undergraduates in delivering technical oral presentations. It is aimed at identifying the effectiveness of the self-assessment strategy in enhancing the engineering undergraduate‟s non-verbal communication skills and to see if there is any statistical correlation between the engineering undergraduates‟ self-assessment scores and the engineering lecturers‟ assessment scores in non-verbal communication skills of Undergraduate Research Project 2 (URP2) final presentations. In addition, the study generated essential findings pertaining to the engineering undergraduates and lecturers‟ perceptions about the use of self-assessment in delivering oral presentations in academic context. The researcher conducted this research with 127 engineering undergraduates of the Faculty of Civil Engineering and Earth Resources, in Universiti Malaysia Pahang (UMP). Quantitative and qualitative approaches were employed to answer the research questions of the current study. The first research question tackles the issue of implementing selfassessment among engineering undergraduates in enhancing non-verbal communication skills. In answering the first research question, the qualitative data revealed important findings pertaining to the engineering undergraduates‟ enhancements after using the assessment in non-verbal communication skills (such as facial expressions, hand gestures, body language, and eye contacts) of URP2 final presentations. In addition, the findings of the second research question revealed a moderate positive correlation between the engineering undergraduates‟ self-assessment scores and the engineering lecturers‟ assessment scores in non-verbal communication skills. The third research question‟s findings indicated that the engineering undergraduates hold positive perceptions towards the use of self-assessment technique in delivering URP2 oral presentations. The positive perceptions depict the significance of this assessment in enhancing their non-verbal communication skills in the engineering undergraduates‟ views and the significance of being good presenters. In the same vein, the final research question of the study investigated the engineering lecturers‟ perceptions regarding the use of self-assessment technique among the engineering undergraduates to develop their non-verbal communication skills and to enhance their presentation skills of URP2. It was demonstrated that the engineering lecturers possessed positive perceptions towards the use of self-assessment among the engineering undergraduates‟ in delivering oral presentations. This study is significant as the issue of understanding and realising the importance of the self-assessment in developing the engineering undergraduates‟ nonverbal communication skills of URP2 final presentations will help lecturers as well as undergraduates in establishing, developing and improving the tertiary undergraduates‟ oral presentations skills. In addition, the study is essential as it may confront the engineering undergraduates‟ presentation weaknesses, and thus, assists them to make successful oral presentations.